Food safety : emerging issues, technologies, and systems - Ricke, Steven C., 1957-; Donaldson, Janet R.; Phillips, Carol A. (Elsevier, 2015)
Food Safety: Emerging Issues, Technologies and Systems offers a systems approach to learning how to understand and address some of the major complex issues that have emerged in the food industry. The book is broad in coverage and provides a foundation for a practical understanding in food safety initiatives and safety rules, how to deal with whole-chain traceability issues, handling complex computer systems and data, foodborne pathogen detection, production and processing compliance issues, safety education, and more. Recent scientific industry developments are written by experts in the fiel.